Bound Soliton Fiber Laser Mode-Locking Without Saturable Absorption Effect - Cheng-Jhih Luo; Sheng-Min Wang; Yinchieh Lai (IEEE Photonics Journal)
Stable bound soliton laser mode-locking is experimentally demonstrated in an environmentally stable hybrid mode-locked Er-doped fiber laser without incorporating (equivalent) nonlinear saturable absorption effects. The laser has a sigma-type cavity and exhibits a higher threshold for single to bound soliton mode-locking state transition. A nonlinear eigenstate analysis based on the master equation model and the concept of steady-state lasing gain is developed to more physically explain the observed mode-locking state transition phenomena.